Coloniality, Elite Networks and Intersectionality: Key Concepts in Understanding Biomedical Power and Equity in Health Policy Processes; Comment on "Power Dynamics Among Health Professionals in Nigeria: A Case Study of the Global Fund Policy Process" - Rakesh Parashar; Veena Sriram; Sharmishtha Nanda; Frayashti Shekhawat (Kerman University of Medical Sciences, 2023)
To understand the role of power in health policy processes in low- and middle-income country (LMIC) contexts, it is necessary to engage with global and local power structures and their historical contexts. In this commentary, we outline three dimensions that shape a dominant power in health policy processes - the biomedical power. We propose that understanding the linkages between medical power and colonialism; the close connection of public health, medicine and elite networks; and the intersectionalities that shape the powers of medical professionals can offer the means to examine the biomedical hegemony in health policy processes. Additionally we suggest that a more nuanced understanding of the interaction of local powers with global funding can offer some entry points to achieving more equitable and interdisciplinary health policy processes in LMICs.